The actor in you twelve simple steps to understanding the art of acting - Benedetti, Robert L. (Pearson Education, Inc., 2015)
The Actor in You presents a thorough and systematic exposure to the fundamentals of the acting process in simple, direct language and a streamlined structure. This title draws on exercises and examples from students' everyday lives, well-known plays, and popular television programs to lead the beginning student through the process of creating a role.